Top spoilage losses in horizontal silos in western Kansas - J.T. Dickerson; G. Ashbell; L. Pfaff; K.K. Bolsen; B.E. Brent; J.E. Bradford; R.L. Smith (Kansas Agricultural Experiment Station Research Reports, 1991)
The top 3 feet from 30 horizontal silos was sampled at three depths to determine top spoilage losses, using ash content as an internal marker. When compared to face samples, corn and forage sorghum silages exhibited similar additional organic matter (OM) losses in the top 18 inches. In the top 18 inches, covering silage reduced spoilage losses of OM from 41 to 27 percentage units compared to uncovered counterparts. Covering corn silage reduced spoilage losses of OM from 49 to 31 and 9 to 1 percentage units in the top and second 18 inches, respectively. Similar reductions in OM losses from covering were observed in the forage sorghum silages. Although spoilage losses observed in covered silages appear high, covering silage stored in horizontal silos greatly reduced the estimated storage losses in the top 3 feet.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Survey; Top spoilage; Silage; Horizontal silos